2020
DOI: 10.20473/jovin.v1i2.23565
|View full text |Cite
|
Sign up to set email alerts
|

Anxietas and Coping Mechanism of the Final Semester Nursing Students in the Situation of Covid-19

Abstract: Introduction: The Covid-19 pandemic which hit 215 countries has an impact on all aspects of life for the world community, including Indonesia. One of the most significant impacts is the world of education. The government policy towards education is to do distance learning or learning from home. This changing learning system raises various problems, especially for nursing students. Competencies that must be mastered by nursing students, especially at the final level, apart from a cognitive perspective, are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…11 The findings of this study is also inconsistent with the study done in Assiut University and Indonesia which showed that nursing students also have severe anxiety along with the mild and moderate level of anxiety. 12,13 The most common symptoms of moderate anxiety were terrified/afraid, nervous and unable to relax which were present among 25%, 24.3% and 20.1% respectively. This finding is consistent with the study done in Assiut University which showed that 21.3% of nursing students had fear and 36.1% were anxious.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 The findings of this study is also inconsistent with the study done in Assiut University and Indonesia which showed that nursing students also have severe anxiety along with the mild and moderate level of anxiety. 12,13 The most common symptoms of moderate anxiety were terrified/afraid, nervous and unable to relax which were present among 25%, 24.3% and 20.1% respectively. This finding is consistent with the study done in Assiut University which showed that 21.3% of nursing students had fear and 36.1% were anxious.…”
Section: Discussionmentioning
confidence: 98%
“…11 The findings of this study is also inconsistent with the study done in Assiut University and Indonesia which showed that nursing students also have severe anxiety along with the mild and moderate level of anxiety. 12 , 13 …”
Section: Discussionmentioning
confidence: 99%